GENDER METAPHOR: A COMPARATIVE ANALYSIS OF MALE AND FEMALE POETS - Simorangkir, Raslima; Wulandari, Vanny; Dalimunte, Vina Fitriani; Putri, Riska Ananda; Rangkuti, Rahmadsyah (JURNAL DARMA AGUNG, 2024)
This research conducts a comparative analysis of the metaphors used in Alfred Lord Tennyson's poem "Tears, Idle Tears" and Emily Dickinson's "After Great Pain, a Formal Feeling Comes." Metaphor is a powerful literary device for conveying emotions and abstract meanings, often reflecting the social context and personal experiences of the poet. It explores how male and female poets confront themes of emotional pain, trauma, and loss, influenced by gender dynamics. Tennyson's work encapsulates nostalgia and loss through romantic imagery, subtly challenging Victorian gender norms by depicting male vulnerability. In contrast, Dickinson’s poem portrays emotional numbness and self-defense following trauma, reflecting the rigid societal expectations on women to maintain composure despite inner turmoil. The research employs a descriptive-qualitative approach to examine how the poets use metaphors to express their emotional states, highlighting the perspective of gender. While Tennyson’s metaphors emphasize existential longing and an introspective view of masculinity, Dickinson's metaphors focus on the suppression of pain and emotional distance, illustrating the social pressures on women to conceal their suffering.